ANALISIS TINDAK TUTUR DALAM PERCAKAPAN PADA MEDIA SOSIAL SISWA SD - Nikmatu Zuhriyah; Gunarti Retnoningrum P; Hendri Hidayat; Decenni Amelia (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
Social media is a type of online media that is used to help people interact with each other through the internet. Social media is not only used to communicate and interact, but also for self-expression and self-branding, such as taking photos and making videos in various styles. This study aims to analyze speech actions carried out by elementary school students in conversations on social media. Social media has become a significant communication space for elementary school students, it affects the way they convey their intentions, information, and emotions. The method used is a literature study. The results of this study show: 1) Characteristics of Elementary School Students' Speech Behavior on Social Media, students always use unique and creative language, they can also express their feelings and thoughts freely, in other social media students always interact with friends and others through comments and messages so that it can foster a social spirit in students. 2) The Impact of Social Media on the Communication Development of Elementary School Students, there is a positive impact, namely that some students can communicate in English because they often see content creators from within and outside the country. The negative impact is that students often speak words using poor language. 3) Implications In Education, students always want to seek information to improve learning achievement.